Management and Performance of Diagnostic Investigations on the Platform of the Specialized Anti-Epidemic Team Mobile Complex During EVD Epidemics in 2014 in the Republic of Guinea - A. Yu. Popova; V. A. Safronov; N. F. Magasuba; D. V. Utkin; G. N. Odinokov; O. V. P’Yankov; A. S. Sergeev; S. A. Bodnev; A. S. Kabanov; V. E. Kuklev; A. A. Lopatin; A. S. Razdorsky; et al. (Проблемы особо опасных инфекций, 2014)
Given is an account of the EVD epidemics that started in the Republic of Guinea in December, 2013 and spread over West African countries within 2014. Established have been the grounds for the Rospotrebnadzor SAET deployment in the Republic of Guinea, objectives, goals and stuffing of the mission, and mobile complex technical performance. Described are the key stages of the work, including the process of integration into the UNMEER. Outlined are priority areas of collaboration with the National Public Health Ministry and international partner organizations. Represented are the results of work on the Ebola fever and other dangerous infectious diseases diagnostics, carried out at the mobile facility. Provided is molecular-genetic characteristics of the Ebola virus.